Optical Design of a Mobile Solution for Multimodal Eye Disease Screening - Santos, Miguel Lourenço (2022)
Diabetic Retinopathy and Glaucoma are pathologies that cause ophthalmic defects and may lead to complete vision loss. This factor, along with being the leading causes of blindness worldwide increases the relevance of early diagnosis and frequent screening actions. Factors such as lack of diagnostic equipment, absence of ophthalmologists or logistical difficulties, make the diagnosis and follow-up of these diseases inadequate, especially in rural and technologically underserved areas. In order to create high-coverage screening solutions, Fraunhofer AICOS has developed the EyeFundusScope - a portable fundus camera prototype for retinal observation and screening of diabetic retinopathy. The work here presented aims to allow the EyeFundusScope to perform pupillometry, empowering it as a tool for glaucoma screening. Besides the optical design, the necessary mechanical and electronic changes have been implemented. The experimental tests provided results in accordance with the goals of the thesis, and theoretical light hazard calculations assured the safety of the illumination system for human eyes. Finally, a protocol for a multimodal acquisition was outlined. In the future, the implementation of the stimulus system will need to be further studied, and, to verify the compliance with the safety standards, the prototype will be submitted to experimental light hazard tests. Also, the implementation of computer vision algorithms for continuous measurement of the pupil size and glaucoma assisted diagnosis will contribute to the establishment of the device as a complete screening tool.